The Making of Long-Lasting Memories: A Fruit Fly Perspective - Roselli, Camilla; Ramaswami, Mani; Boto, Tamara; Cervantes-Sandoval, Isaac (Frontiers in Behavioral Neuroscience, 2021)
Understanding the nature of the molecular mechanisms underlying memory formation, consolidation, and forgetting are some of the fascinating questions in neuroscience. The encoding, stabilization and elimination of memories, rely on the structural reorganization of synapses. These changes will enable the facilitation or depression of neural activity in response to new information acquisition. In other words, these changes affect the weight of specific nodes within a neural network. We know that these plastic reorganizations require de novo synthesis of proteins in the context of long-term memory. This process depends on neural activity triggered by the learned experience. The use of model organisms like Drosophila melanogaster has been proven essential for advancing our knowledge in the field of neuroscience. Flies offer an optimal combination of a more straightforward and more approachable nervous system while still displaying complex behaviors. Studies in Drosophila neuroscience, which expanded over several decades, have been critical for understanding the cellular and molecular mechanisms leading to the synaptic and behavioral plasticity occurring during learning and memory. This is possible thanks to the sophisticated technical approaches that enable neural manipulation, like chemogenetics, thermogenetics, or optogenetics, and the precise control of gene expression in the fruit fly. The search for the identity of genes expressed as a result of memory acquisition has been an active interest since the origins of behavioral genetics. Here we review recent literature regarding how the formation of memories induces a rapid, extensive, and transient wave of transcription and translation. The complexity of the circuitry involved in memory formation and consolidation is such that there are localized changes in neural activity. Different types of neurons are recruited at different times into memory traces. In long-term memory, the synthesis of new proteins is required in specific subsets of cells. This de novo translation can take place in the somatic cytoplasm and/or locally. We will also review recent advances in understanding how space-specific changes are confined to the relevant synapse. These recent studies have led to exciting discoveries regarding proteins that were not previously involved in learning and memory processes. This invaluable information will lead to future functional studies.